Determinantes para empresas multinacionais de médio porte a adoção das IFRS FULL ou da IFRS SME e a definição de suas políticas contábeis - Medina, Renata de Souza Ferreira (2015)
The general objective of this study is to identify what factors lead medium-sized multinational companies to adopt IFRS Full or IFRS SME. In order to do so, the Institutional Theory was applied as research basis since it provides theoretical ground for the identification of the reason why companies make such a choice. This work also sought to identify which institutional changing mechanisms, whether coercive, mimetic and/or normative, are present when companies look for legitimacy in the process of adopting norms. The sample presented here comprises eight professionals responsible for decision making in accounting processes working for the referred companies, selected according to an availability criteria. This researched was carried out applying semi-structured interviews, which allow a deeper investigation of the issue. Collected material has been analyzed through Bardin's Technical Analysis of Content (2007). From the results, it was possible to identify that the companies have the IFRS Full as their first choice. It was also found that such decision is bound to the technical skill of the professional in charge, along with the growing perspective for the company within a short term. The professionals working in such companies do not analyze the available accounting choices in both cases, demonstrating that there is no relationship between the choice made and the evaluation of the model that best suits operations and results. Little prioritization/relevance by companies in adopting norms, as well as little interference by third parties and little interference by the mother company were found as inhibiting factors. As for the encouraging factor, the study found that the capacity of the professional in charge responds for the adoption of norms, which takes place as a result of normative and mimetic pressure when companies search for legitimacy. In addition, we submitted the results of this research to the Accounting Council (CRC SP) and the Big Four consulting firm, in order to have them validated and deepened, since those two have been often mentioned by the professionals. Such consulting raise aspects mostly approached by the professionals, i.e. the need for a more effective professional class representation and a support from auditing firms with the board of directors of the companies studied, in order to propel the processes of adopting norms and also to generate a sense of responsibility by the companies in such processes, besides holding the accounting professionals responsible.